2017
DOI: 10.1002/jcp.25801
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs: Potential candidates for diagnosis and treatment of colorectal cancer

Abstract: Colorectal cancer (CRC) is known as the third common cancer worldwide and an important public health problem in different populations. Several genetics and environmental risk factors are involved in the development and progression of CRC including chromosomal abnormalities, epigenetic alterations, and unhealthy lifestyle. Identification of risk factors and biomarkers could lead to a better understanding of molecular pathways involved in CRC pathogenesis. MicroRNAs (miRNAs) are important regulatory molecules wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
172
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 181 publications
(173 citation statements)
references
References 134 publications
1
172
0
Order By: Relevance
“…It has been demonstrated that miRNAs are crucial for the occurrence and development of CRC (29,30). Through bioinformatics analysis, we identified CXCL11 as a potential target of miR-144.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that miRNAs are crucial for the occurrence and development of CRC (29,30). Through bioinformatics analysis, we identified CXCL11 as a potential target of miR-144.…”
Section: Discussionmentioning
confidence: 99%
“…MiRNAs regulate several biological processes such as growth, development, angiogenesis, stem cell renewal, and differentiation (Banikazemi et al, ; Golabchi et al, ; Jafari et al, ; Masoudi, Mehrabian, & Mirzaei, ; H. Mirzaei, Ferns, Avan, & Mobarhan, ; H. Mirzaei, Yazdi, Salehi, & Mirzaei, ; Saeedi Borujeni et al, ; Simonian, Mosallayi, & Mirzaei, ; Tavakolizadeh et al, ). Deregulation of these molecules is associated with initiation and progression of many diseases such as cancer, diabetes, stroke, neurodegenerative diseases, and cardiovascular diseases (Gholamin et al, , ; Hoseini et al, ; H. Mirzaei, Gholamin, et al, ; H. R. Mirzaei, Sahebkar, et al, ; H. Mirzaei, Naseri, et al, ; H. Mirzaei, ; H. Mirzaei, Fathullahzadeh, et al, ; H. Mirzaei, Momeni, et al, ; H. R. Moridikia et al, ; Rabieian et al, ; Rashidi, Malekzadeh, Goodarzi, Masoudifar, & Mirzaei, ; Rashidi, Hoseini, Sahebkar, & Mirzaei, ). Recently, alterations in some specific miRNAs in AD brains have been revealed by scrutinizing the miRNA expression profiles.…”
Section: Mirnas As Therapeutic Candidate In Admentioning
confidence: 99%
“…miRNAs are a group of noncoding RNAs, which act epigenetic players. Given that these molecules can affect a wide range of biological processes, such as growth, angiogenesis, differentiation, metastasis, and differentiation of stem cells . Given that deregulation of miRNAs are related with initiation and progression of a large number of diseases, such as cancer, diabetes, stroke, cardiovascular diseases, viral infections, and degenerative diseases .…”
Section: Mirna and Response To Therapy In Leukemiamentioning
confidence: 99%